Geological and Geophysical Observations to Determine the Gas Seepage Source of Titas Gas Field Region, Bangladesh - Bijoy, Sourov Datta; Gazi, Md Yousuf; Kabir, SM Mainul; Imam, Badrul (Journal of the Asiatic Society of Bangladesh, Science, 2019)
Titas Gas Field, the largest gas field in Bangladesh, has been encountering gas seepages in numerous points at the surface in an area of about 7 sq. km. at the southeastern part of the field since 2006. Gas has been seeping through the water wells, small and large holes in the fields including agricultural lands, in the river and through the cracks in the ground. The present research attempts to point out the source of the gas seepages based on the field studies, wireline log analyses and other available borehole data. A reconnaissance resistivity survey has been carried out around the high seepages area to detect any evidence of shallow subsurface fault. No fault was detected by resistivity survey in the shallow depth in the seepage area and thus fault as a conduit for the seepage could not be confirmed. Primarily, all wells of Titas Well Location (TWL-C) (Titas-06, 08, 09 and 10) were suspected as possible source wells as the surface distribution of seepages generally clusters around TWL-C. Titas-06 and Titas-08 were taken out of suspect list as the gas seepage distributions do not follow well path and cement bonding against reservoir sands including ‘A’ sand in these two wells are also good. Gas seepages follow the well trajectories of Titas-09 and 10 wells but cement bonding against ‘A’ gas sand in Titas-09 also discarded the well as a probable source of the gas seepage. Also, the suggestion that Titas well-03 could be a source of gas seep is also ruled out because of the fact that it is located 3 km away from the seepage area, there is no evidence of any seepage in between the well 3 and the seepage area, and the gas sands are also well protected. The above evidences turned the whole focus onto Titas-10. Gamma ray, resistivity, density, sonic and neutron log signatures recorded initially in the Titas-10 well strongly indicated a major gas sand and has been designated ‘A1’ gas sand. On the basis of various logs including CBL/VDL log it is evident that about 23 meters (3157-3180-meter MD) gas sand at the top which is not protected by cement. It is most likely source of gas seeps in Titas gas field is the gap in the cement protection at the top of A sand in Titas-10 well. Asiat. Soc. Bangladesh, Sci. 45(1): 93-109, June 2019